Oddziaływanie programu LEADER na kapitał społeczny mieszkanek wsi - Zajda, Katarzyna; Psyk-Piotrowska, Elżbieta (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2014)
In the article there is an analysis of the impact of the LEADER approach on the social capital of rural women involved in the local action groups. The aim of the article is to characterize the features of this capital taking into consideration the capital belonging to men involved in these organizations. The question is whether the role of local action groups as far as the social capital is concerned equally applies to women and men associated in these structures. On the basis of the research carried out in 2011–2013 (on a sample of 238 women and 327 men) within the framework of the project entitled: “Structure and determinants of social capital of local action groups” (National Science Centre grant) women social capital analysis was made (with its definition by R. Putnam). In the social survey distributed surveys technique was used. The result of the analysis is a statement that women social capital differs from men social capital mainly in the area of trust component and network component.